1996
DOI: 10.1021/ie950759x
|View full text |Cite
|
Sign up to set email alerts
|

Steam Activation of a Bituminous Coal in a Multistage Fluidized Bed Pilot Plant:  Operation and Simulation Model

Abstract: A hydrodynamic and kinetic model was developed and applied to simulate the experimental data from a three-stage fluidized bed pilot plant with downcomers. This was used to study the activated carbon production from a Spanish bituminous coal by steam gasification. The steam gasification kinetics, considering the influence of inhibitors, were also determined in a thermobalance. With the kinetic equation and the experimental solids residence time distribution of the pilot plant, the model simulates the overall pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In the same way, TGA is a useful tool to study charcoal gasification, since it provides accurate data about charcoal reactivities under active atmospheres (CO 2 , oxygenated mixtures or steam). Literature about this subject is also extent [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, TGA is a useful tool to study charcoal gasification, since it provides accurate data about charcoal reactivities under active atmospheres (CO 2 , oxygenated mixtures or steam). Literature about this subject is also extent [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, TGA is a useful tool to study devolatilized charcoal gasification since it provides accurate data about charcoal reactivities under active atmospheres (CO 2 , oxygenated mixtures or steam) (e.g. [12][13][14][15]). However, thermogravimetric studies of the raw materials under oxidative atmosphere are not so frequent in spite of the information about incineration processes that can be obtained from this technique, and the number of studies has increased [8,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This gas needs to be counted as an air emission. Previous LCA studies have assumed that the only steam-carbon reaction occurs without CO 2 generation, which is not consistent with experimental measurements. , Other reactions such as the water–gas shift reaction, methanation reactions, steam-reforming reactions, and the Boudouard reaction also occur. , In this study, those reactions were considered by using the model from Martı́n-Gullón et al as shown in eq . The Aspen Plus database has property data, which can be used to model gas-phase reactions and estimate the reaction products including gases (e.g., hydrogen, methane, carbon monoxide and carbon dioxide) and vapors (e.g., alkanes, alkenes and oxygenates). , However, the property data for solid components (e.g., woody biomass, biochar, and AC), lignocellulosic components (e.g., cellulose, hemicellulose and lignin) and monosaccharides (e.g., glucose and xylose) are not included in Aspen databases. The relevant physical property parameters for lignocellulosic components and monosaccharides were collected from the literature .…”
Section: Methodsmentioning
confidence: 95%
“…13,33 Other reactions such as the water−gas shift reaction, methanation reactions, steam-reforming reactions, and the Boudouard reaction also occur. 64,65 In this study, those reactions were considered by using the model from Martı ́n-Gulloń et al 66 as shown in eq 3.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%